2013
DOI: 10.1016/j.expneurol.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sensory neuron growth cone and filopodial responses to structurally diverse aggrecan variants, in vitro

Abstract: Following spinal cord injury, a regenerating neurite encounters a glial scar enriched in chondroitin sulfate proteoglycans (CSPGs), which presents a major barrier. There are two points at which a neurite makes contact with glial scar CSPGs: initially, filopodia surrounding the growth cone extend and make contact with CSPGs, then the peripheral domain of the entire growth cone makes CSPG contact. Aggrecan is a CSPG commonly used to model the effect CSPGs have on elongating or regenerating neurites. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…The fold change in neurite outgrowth was the same regardless of substrates, but the absolute growth was still not as robust as neurons replated onto control substrates. Thus, the reduced absolute growth on CSPGs is not likely a result of impaired activation or inactivation of the pro-regenerative program, but instead may be due to activation of distinct pathways to inhibit neurite outgrowth (Beller et al, 2013; Dickendesher et al, 2012; Fisher et al, 2011; Hur et al, 2011; Monnier et al, 2003; Shen et al, 2009; Sivasankaran et al, 2004). This highlights the important need to target both intrinsic and extrinsic mechanisms to achieve effective regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The fold change in neurite outgrowth was the same regardless of substrates, but the absolute growth was still not as robust as neurons replated onto control substrates. Thus, the reduced absolute growth on CSPGs is not likely a result of impaired activation or inactivation of the pro-regenerative program, but instead may be due to activation of distinct pathways to inhibit neurite outgrowth (Beller et al, 2013; Dickendesher et al, 2012; Fisher et al, 2011; Hur et al, 2011; Monnier et al, 2003; Shen et al, 2009; Sivasankaran et al, 2004). This highlights the important need to target both intrinsic and extrinsic mechanisms to achieve effective regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These cultures can be used for specifically analyzing growth cones in addition to analyzing the entire neuron. Previously, this procedure has been used to evaluate growth cone velocity and behaviors, such as growth cone collapse 8,9,11,13,16 . Lower plating densities on these coverslips results in dead neurons that are not adhered to the substrata.…”
Section: Representative Resultsmentioning
confidence: 99%
“…For example, intracellular levels of cAMP and surface levels of integrins are significantly different in neurons plated on these two substrata 7,8 . Additional studies have shown that other molecules, including fibronectin and chondroitin sulfate proteoglycans, impact the expression of cell surface molecules and neuronal motility [7][8][9][10][11] . In addition, soluble molecules such as neurotrophins and neurotropins also impact cell membrane composition and neuronal motility [12][13][14][15][16] and can be easily and accurately manipulated in a cell culture model.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise composition of the tissue existing within the lesion environment was not identified in this study, there was a robust density of CSPGs and IBA-1 labeled cells in the tissue within the lesion site. As CSPGs have been reported to lead to the collapse of the growth cone, the fact that the transplant/lesion site was dense in CSPGs, while also containing a greater labeling of GAP-43 in SDF-1-MSC-treated animals, creates a perplexing contradiction (Beller et al, 2013;Schmalfeldt, Bandtlow, Dours-Zimmermann, Winterhalter, & Zimmermann, 2000). Such findings are suggestive that the secretome of MSCs, particularly when enhanced with SDF-1␣ expression, can help overcome the inhibitory nature that CSPGs exert on growth and regeneration.…”
Section: An Stewart Et Al / Sdf-1 Overexpression By Mesenchymal Stmentioning
confidence: 99%